Case Report: MDFIC gene mutation resulting in central conducting lymphatic anomaly facilitates group A Streptococcus sepsis - Weidner, Johannes; Fiedler, Kai; Schulze-Becking, Mechthild; Sentner, Christiaan Peter; Korenke, Christoph; Heep, Axel (Frontiers in Pediatrics, 2024)
Background Central conducting lymphatic anomaly (CCLA) is a heterogeneous disorder characterized by structural anomalies in the main collecting lymphatic vasculature. These anomalies result in chronic chylous leaks, causing issues such as congenital hydrothorax and potentially impairing the normal immune response. Recently, mutations in the MyoD family inhibitor domain-containing (MDFIC) gene have been identified as a cause of CCLA. Group A Streptococcus infections are common, and timely identification of patients at risk for severe complications is crucial. Case presentation Here, we present the case of a 13-year-old female patient with CCLA associated with an MDFIC mutation, who suffered from a severe group A Streptococcus sepsis. Initially, the patient was unresponsive to aggressive fluid resuscitation. Although the course of the sepsis was severe, standardized treatment according to the surviving sepsis campaign proved effective in stabilizing the patient. Discussion The patient's MDFIC mutation may have contributed to the severe clinical course of the sepsis. It is theorized that this mutation affects the function of the immune system both indirectly, by causing CCLA, and directly, by potentially influencing transcriptional activity in immune cells. More research on the effect of MDFIC mutations on immune responses is required.